Viral hepatitis in women of reproductive age - И. А. Зайцев (Publishing House TRILIST, 2017)
A considerable number of various liver diseases that are associated with the course of pregnancy are quite common and occur at least three percent of pregnant women. This pathology plays an important role and is one of the most important reasons for the development of a wide range of different pathologies in pregnant women, in fetuses and newborns. The problem of changing functional liver tests during pregnancy acquires special sharpness and significance in connection with the not-so-recent role of liver pathology in mortality in maternal and perinatal mortality. In recent years, based on a large number of observations and statistical data, important information has been obtained on the details of the mechanism of this pathology, developed and refined diagnostic methods, as well as detailed schemes for treating liver diseases in pregnant women at different stages of pregnancy. Collected and scrupulously processed extensive data on the change in a variety of functional liver tests at various stages of pregnancy, both under normal and with complicated flow. Particular attention is paid to such pathology as preeclampsia, eclampsia, acute fatty liver disease of pregnant women, HELLP syndrome, intrahepatic cholestasis of pregnant women, uncontrollable vomiting of pregnant women, liver rupture, in the diagnosis of which one of the leading, decisive roles is assigned to the change in functional liver tests. In our review, the main emphasis was made in the direction of changing various significant indicators of functional hepatic tests in pregnant women both in physiologically developing pregnancy and in various liver diseases, both as a consequence of pregnancy and not directly related to it. The article also highlights the main mechanisms of these changes. The publication provides the latest information on the timing of full or partial normalization of a wide range of functional liver tests both after delivery and in the natural course of the disease.